Effects of state-led suburbanization on traffic crash density in China: Evidence from the Chengdu City Proper. (December 2020) - Qiao, Si; Gar-On Yeh, Anthony; Zhang, Mengzhu; Yan, Xiang
Highlights: China's post-2008 suburbanization promotes traffic safety in the suburb. NACD tends to get lower with high mixed land use and high-density expressway. In Chengdu City Proper, the suburb tends to have lower crash density than inner-city by 26.9 %. Abstract: Road crashes have become a leading cause of death in China. Although enormous efforts have been exerted to determine the factors that affect individual crash incidents, neighborhood-level crash incidence in Chinese cities has not been sufficiently analyzed. This study fills this gap by quantifying the effects of built environment factors on neighborhood-level automobile-involved crash density (NACD) in urban China and identifying its mediators and mediating effects. In American suburbs, urban sprawl is widely recognized to render neighborhoods unsafe for residence, thus leading to a high crash incidence. This study compares the characteristics of built environments between inner-city neighborhoods and the new neighborhoods that have been developed through China's state-led suburbanization since 2008 to reveal how this suburbanization provides a safer neighborhood environment. A structural equation model is used to examine the relationships among suburbanization, built environment factors, and NACD in the city proper of Chengdu, the largest metropolis in southwest China. Thus, this study contributes new empirical evidence to the debates over urban designs that are safest for traffic. Moreover, this study enriches our understanding of different sociospatial consequences between American-style urban sprawl and China's state-led suburbanization.